2022
DOI: 10.3390/cells11030538
|View full text |Cite
|
Sign up to set email alerts
|

ISG15 and ISGylation in Human Diseases

Abstract: Type I Interferons (IFNs) induce the expression of >500 genes, which are collectively called ISGs (IFN-stimulated genes). One of the earliest ISGs induced by IFNs is ISG15 (Interferon-Stimulated Gene 15). Free ISG15 protein synthesized from the ISG15 gene is post‑translationally conjugated to cellular proteins and is also secreted by cells into the extracellular milieu. ISG15 comprises two ubiquitin-like domains (UBL1 and UBL2), each of which bears a striking similarity to ubiquitin, accounting for its earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 222 publications
(412 reference statements)
0
33
0
Order By: Relevance
“…ISGylation is rarely induced under physiological conditions whereas abnormally elevated in various human diseases including several types of cancer. 43 ISGylation can be induced in many patterns in cancer. Firstly, ISGylation can be induced by type I interferon (IFN) produced in the tumour microenvironment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ISGylation is rarely induced under physiological conditions whereas abnormally elevated in various human diseases including several types of cancer. 43 ISGylation can be induced in many patterns in cancer. Firstly, ISGylation can be induced by type I interferon (IFN) produced in the tumour microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…ISGylation is rarely induced under physiological conditions whereas abnormally elevated in various human diseases including several types of cancer 43 . ISGylation can be induced in many patterns in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of ISG15 are correlated with a number of human ailments such as cancer, neurodegeneration, inflammation, and assaults from pathogens [74] , [75] . Indeed, IFN has been used to treat certain types of cancer and specific viruses [76] .…”
Section: The Anti-viral Role Of Isg15mentioning
confidence: 99%
“…For instance, the UBL protein HLA-F adjacent transcription 10 (FAT10) suppresses the RIG-I-TRIM25 complex through binding and stabilizing the RIG-I protein, thereby dampening the RIG-I-mediated antiviral responses[ 111 ]. The other UBL protein, IFN-induced 15-kDa protein (ISG15), performs ISGylation (a ubiquitin-like modification) and activates MDA5 but reduces RIG-I intracellular levels [ [112] , [113] , [114] ]. Intriguingly, it has been recently found that SARS-CoV-2 utilizes autogenous papain-like protease to antagonize MDA5 ISGylation and evade host innate immunity, which may account for the SARS-CoV-2 immune evasion and the suppression of host IFN-I production[ 115 ].…”
Section: Regulation Of Rlr Signaling Cascadementioning
confidence: 99%